PENERAPAN METODE PENEMUAN TERBIMBING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 2 KOTA BENGKULU - Devi Yunita; Effie Efrida Muchlis; Dewi Rahimah; Nanda Lorenza (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2023)
Mathematics learning in schools more often uses the lecture method and does not provide opportunities for students to construct their knowledge. In learning, students tend to be passive in receiving material from the teacher because students only memorize formulas instead of understanding them so that students' interest in learning mathematics is low. This resulted in the low learning outcomes of students' mathematics. This study aims to determine how to apply the guided discovery method so that there is an increase in students' learning activities and mathematics outcomes. This type of research is classroom action research (CAR) with data collection techniques through student activity observation sheets and learning outcomes tests. The research subjects were all students of class VIIIG SMPN 2 Bengkulu City. The results showed that the application of the guided discovery method could improve students' learning activities and mathematics outcomes. The increase in activity and student learning outcomes can be seen from the increase in the average score of two observers where in the first cycle, namely 27 (sufficient criteria), the second cycle increased to 39 (good criteria), and the third cycle increased again to 46.5 (good criteria). Meanwhile, the increase in student learning outcomes can be seen from the increase in the average score of students from cycle I to cycle III, namely: 73.3; 79.1; and 85.81 with the percentage of classical learning completeness from cycle I to cycle III, namely: 52.78%; 72.22%; and 94.44%.